ECOSYSTEM ANIMATION VIDEO (VISIKO) AS MEDIA IN LEARNING ECOSYSTEM MATERIAL IN THE FIFTH GRADE: A RESEARCH AND DEVELOPMENT - Aliyah, Muhimatul; Sofiyana, Marinda Sari; Putriani, Ida (JOSAR (Journal of Students Academic Research), 2024)
The results of observations and interviews revealed that the use of learning media is still lacking, with most teachers only relying on the lecture method. This study aims to evaluate the effectiveness of VISIKO (Ecosystem Animation Video) teaching media in teaching ecosystem material to grade V students. This type of research follows the RnD method developed by Sugiyono, with limitations up to the seventh stage, namely product revision. The feasibility assessment of learning media is carried out by a number of experts, including material experts, media experts, and linguists. In addition, the readability score of VISIKO teaching media was tested by involving 10 representative students from grade 5 at SDN Sumberjo 01, as well as 5 teachers from SDN Sumberjo 01, SDN Bajang 01, and SD Alam Al Ghifari Blitar. The results showed that VISIKO (Video Animation Ecosystem) teaching media products received high feasibility scores from various validators, namely material experts by 87.6%, media experts by 98.8%, and linguists by 91.4%. With an average eligibility percentage of 92.6%, this product can be considered very viable. Limited trials involving teachers also resulted in a readability rate of 92.8%, while students gave a readability score of 97.7%. Based on teacher and student assessments, this product is considered very good and very easy to understand, making it suitable for use in learning ecosystem materials for grade 5 students.